Antisense oligonucleotides targeted to the domain IIId of the hepatitis C virus IRES compete with 40S ribosomal subunit binding and prevent in vitro translation - Tallet-Lopez, Béatrice (Oxford University Press, 2003)
Initiation of protein synthesis on the hepatitis C virus (HCV) mRNA involves a structured element corresponding to the 5′ untranslated region and constituting an internal ribosome entry site (IRES). The domain IIId of the HCV IRES, an imperfect RNA hairpin extending from nucleotides 253 to 279 of the viral mRNA, has been shown to be essential for translation and for the binding of the 40S ribosomal subunit. We investigated the properties of a series of antisense 2′-O-methyloligoribonucleotides targeted to various portions of the domain IIId. Several oligomers, 14–17 nt in length, selectively inhibited in vitro translation of a bicistronic RNA construct in rabbit reticulocyte lysate with IC(50)s <10 nM. The effect was restricted to the second cistron (the Renilla luciferase) located downstream of the HCV IRES; no effect was observed on the expression of the first cistron (the firefly luciferase) which was translated in a cap-dependent manner. Moreover, antisense 2′-O-methyloligoribonucleotides specifically competed with the 40S ribosomal subunit for binding to the IRES RNA in a filter- retention assay. The antisense efficiency of the oligonucleotides was nicely correlated to their affinity for the IIId subdomain and to their ability to displace 40S ribosomal subunit, making this process a likely explanation for in vitro inhibition of HCV-IRES-dependent translation.